1999
DOI: 10.1002/hep.510300429
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus core protein binds to apolipoprotein AII and its secretion is modulated by fibrates

Abstract: Hepatitis C virus (HCV) is the major etiologic agent of post-transfusion and sporadic non-A, non-B hepatitis. 1 Persistent HCV infection, which develops in at least 70% to 80% of infected patients, often progresses to chronic hepatitis and is highly correlated with the development of cirrhosis and hepatocellular carcinoma. 2-4 Neither a vaccine, nor effective therapy are currently available for HCV, other than interferon alfa combined with ribavirin. 5,6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
118
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 67 publications
(97 reference statements)
4
118
1
3
Order By: Relevance
“…We analysed the sub-cellular localisation of core and PKR. Core showed a cytoplasmic localisation consistent with that previously reported in di erent cell lines (Barba et al, 1997;Sabile et al, 1999;Yasui et al, 1998). Confocal analysis revealed co-localization, in the presence or absence of IFNa treatment (data not shown), of cores expressed from the tumor-derived sequences (AT1, BT1 and BT2), and not the non tumor-derived sequences-(ANT1, ANT2 and BNT1), and PKR (Figure 2a).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We analysed the sub-cellular localisation of core and PKR. Core showed a cytoplasmic localisation consistent with that previously reported in di erent cell lines (Barba et al, 1997;Sabile et al, 1999;Yasui et al, 1998). Confocal analysis revealed co-localization, in the presence or absence of IFNa treatment (data not shown), of cores expressed from the tumor-derived sequences (AT1, BT1 and BT2), and not the non tumor-derived sequences-(ANT1, ANT2 and BNT1), and PKR (Figure 2a).…”
Section: Resultssupporting
confidence: 90%
“…Several studies have in particular established that HCV core, a 191 amino acid basic protein with RNA binding activity, regulates important cellular signals, such as those which control NF-kB-, AP 1-and SRE-activities, MAP kinases, raf, P53 and P21 (Lai and Ware, 2000;Marusawa et al, 1999;Otsuka et al, 2000;Tsuchihara et al, 1999). HCV core has been described as being associated with lymphotoxin-b receptor, TNF-receptor 1, apolipoprotein AII, hnRNP and a bZIP transcription factor (Barba et al, 1997;Chen et al, 1997;Hsieh et al, 1998;Sabile et al, 1999). Evidence exists that HCV core may have an e ect upon cell transformation (Jin et al, 2000) and apoptosis (Marusawa et al, 1999;Ray et al, 1996Ray et al, , 1998Ruggieri et al, 1997); however, the biological consequences of core ectopic expression depend on the levels of expression achieved, the cell type utilized and the cellular environment (Honda et al, 2000;Zhu et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…These in vitro studies, occurring in genotype-1-derived constructs, have suggested that these proteins may interact directly with cytoplasmic lipid structures, specifically apoA1 and apoA2, altering lipid metabolism. 6,7 Inhibition of microsomal triglyceride transfer protein also has been shown, resulting in impaired fat trafficking. 8 This finding is supported in human studies showing decreased apoB levels, a component of very low-density lipoprotein, in patients with significant hepatic steatosis.…”
Section: Steatosis Mediated Via Hepatitis C Virusmentioning
confidence: 99%
“…In addition to forming the viral nucleocapsids, core protein affects a whole array of host cell functions, including apoptosis, cell transformation, signal transduction, and transcriptional regulation (reviewed in references 73 and 78). In addition to cytoplasmic and nuclear localization, the HCV core protein is also secreted from stably transfected cells and has been found in the bloodstream of infected individuals, where it may provide an infection-inde-pendent mechanism of immune dysregulation (31,62). Coreinduced immune dysregulation includes suppression of Th1 polarization, inhibition of IFN-␥-mediated cytotoxic T-lymphocyte (CTL) activation, and decreased interleukin-2 (IL-2) and IL-12 production (for a review, see reference 61).…”
mentioning
confidence: 99%